2010
DOI: 10.2478/10004-1254-61-2010-2022
|View full text |Cite
|
Sign up to set email alerts
|

Content of Toxic and Essential Metals in Medicinal Herbs Growing in Polluted and Unpolluted Areas of Macedonia

Abstract: The aim of this study was to determine and compare Ba, Cr, Cd, Fe, Sr, Pb, and Zn content in medicinal herbs Urtica dioica L., Taraxacum offi cinale, and Matricaria recutita growing in polluted and unpolluted areas of the Republic of Macedonia. The metal content was determined using inductively coupled plasma atomic emission spectroscopy (ICP-AES). In the unpolluted area of Mt. Plačkovica the metal content in Taraxacum offi cinale was in the descending order: Fe>Sr>Zn>Ba>Cr, while Pb and Cd were below the limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(28 reference statements)
0
5
1
1
Order By: Relevance
“…The Pb and Cd concentrations in our study fall within these toxic ranges. They are, however, lower than those found by Gjorgieva et al (2) for Urtica dioica growing in polluted areas of Macedonia (102.03 mg kg -1 for Pb and 7.37 mg kg -1 for Cd) and comparable to those reported by Nadgórska-Socha et al (34) for Plantago lanceolata growing in polluted areas of Poland (19.5 to 121.3 mg kg -1 for Pb, and 5.7 to 13.8 mg kg…”
Section: Plant Contaminationcontrasting
confidence: 55%
See 1 more Smart Citation
“…The Pb and Cd concentrations in our study fall within these toxic ranges. They are, however, lower than those found by Gjorgieva et al (2) for Urtica dioica growing in polluted areas of Macedonia (102.03 mg kg -1 for Pb and 7.37 mg kg -1 for Cd) and comparable to those reported by Nadgórska-Socha et al (34) for Plantago lanceolata growing in polluted areas of Poland (19.5 to 121.3 mg kg -1 for Pb, and 5.7 to 13.8 mg kg…”
Section: Plant Contaminationcontrasting
confidence: 55%
“…Heavy metals in herbal medicines and spices, especially if cultivated or collected in contaminated areas, often exceed safety limits and are an important source of exposure through diet (1)(2)(3)(4). Accumulation of heavy metals in plants (i.e.…”
mentioning
confidence: 99%
“…Cadmium concentration in this study range from 0.001 ± 0.00 mg/kg (Ocimum gratissimum) at the residential area to 2.00 ± 1.56 mg/kg at the industrial area (Azadiractha indica). The level of Cd in this study is well below 0.20 to 16 mg/kg in Urtica dioica, Hypericum perforatum, Achillea millefolium, and Plantago lanceolata around a smelter at Slovenia (Glavac et al, 2017), 5.70 to 13.8 mg/kg in Plantago lanceolata at polluted areas of Poland (Nadgorska-Socha et al, 2013) and 7.37 mg/kg in Urtica dioica at polluted areas of Macedonia (Gjorgieva et al, 2010) but higher than 0.1 to 1.11 mg/kg for Cd in Petroselinum crispum, Ocimum basilicum, Salvia officinalis, Origanum vulgare, Mentha spicata, Thymus vulgaris, and Matricaria chamomilla in the United Arab Emirates, UAE (Dghaim et al, 2015). The level of Cd in our study is well above the permissible limit (PL) 0.3 mg/kg set by FAO/WHO (2006) for medicinal plants and herbs.…”
Section: Means In a Column With Different Superscript Are Significantmentioning
confidence: 57%
“…The concentration of Pb increased from 0.15 ± 0.07 mg/kg (Vernonia amygdalina) at the residential area to 4.58 ± 0.51 mg/kg at the industrial area (Mangifera indica). The level of Pb in this study is higher than 0.25 ± 0.00088 to 2.34 ± 0.0173 ppm (Kulhari et al, 2013) but well below 1.1 to 195.9 mg/kg in Urtica dioica, Hypericum perforatum, Achillea millefolium, and Plantago lanceolata around a smelter at Slovenia (Glavac et al, 2017), 1.0 to 23.52 mg/kg in Petroselinum crispum, Ocimum basilicum, Salvia officinalis, Origanum vulgare, Mentha spicata, Thymus vulgaris, and Matricaria chamomilla in the United Arab Emirates, UAE (Dghaim et al, 2015), 19.50 to 121.3 mg/kg in Plantago lanceolata at polluted areas of Poland (Nadgorska-Socha et al, 2013), and 102.3 mg/kg in Urtica dioica at polluted areas of Macedonia (Gjorgieva et al, 2010). The level of Pb in our study is below the permissible limit (PL) 10 mg/kg set by Codex Alimentarius Commission, FAO/WHO (2006) for medicinal plants and herbs.…”
Section: Means In a Column With Different Superscript Are Significantmentioning
confidence: 99%
“…It was reported that sometimes metals are intentionally added to Asian herbal preparations, because the traditional Indian (Ayurvedic) and Chinese medicine believe in their therapeutic properties (Gjorgieva et al 2010). …”
Section: Effects On Quality Featuresmentioning
confidence: 99%